Patient selfcare with arterial hypertension and its relation to sociocultural and individual factors in patients who were taken care of in a Huancayo hospital - Suasnabar Cueva , Edith (2020)
OBJECTIVE:  To  determine the  practice of  self  and its  relation  to  individual   and   sociocultural factors in hypertensive patients treated at a hospital in Huancayo. METHOD:  Consisted  of  50  patients treated  at  the hypertension program  at  a  hospital in  the   city  of Huancayo. This  study was  descriptive-correlational, not experimental. RESULTS:  We  found   that   the   levels   of   self-care of patients who  participated in the  study are characterized as having  an  average level  (68.00%), only 22.00%  had  a high level and  10.00%  had  a level Low. Regarding individual factors High level (48.00%) and  means (42,00%)  level  was  found. Sociocultural levels  of  hypertensive patients were  Alto  (50.00%), Medium (44.00%)  and  only a minority  (6.00%)  had  a low level. These results allowed us  to conclude that: There is a direct and significant relationship between the  self  and  the  individual  and  sociocultural factors of hypertensive patients in the hypertension program at a hospital in Huancayo, for a significance  level of α = 0.05.